Lipid biomarkers as organic matter source indicators of estuarine mangrove ecosystems. Issue 6 (3rd July 2022) - Ratheesh Kumar, C. S.; Gayathry, O. S.; Rakesh, V. B.; Sudha, A.; Mohan, Roshni; Salas, P. M.; Resmi, P.; Joseph, Manju Mary; Shameem, K.; Chandramohanakumar, N.
ABSTRACT: Surface sediments from three mangrove forests and three adjoining stations of the Cochin estuary were analysed for lipid biomarkers along with bulk parameters to delineate organic matter (OM) sources. Fine-grained sediments dominated in mangrove forests due to low hydrodynamic energy conditions compared to estuaries. The protein/carbohydrate ratio >1 at most of the sites implied that a major fraction of OM was freshly originated. Lipid/carbohydrate ratios >1 indicated the better food quality of OM. Depleted δ 13 C, higher organic carbon-to-nitrogen ratios (>20), tannin and lignin content and lipid biomarkers implied OM inputs from mangrove vegetation. Occurrence of unique mangrove biomarkers like taraxerol in estuarine sediments reflected mangrove input via tidal export of OM. Prominent relative abundance of steroidal ketones, triterpenoid ketones and other degraded triterpenoids pointed towards active diagenetic transformations of sedimentary OM. Significantly higher content of biochemical components and biomarkers in mangrove systems was due to the dominance of fine-grained sediments and better preservation of OM under anoxic conditions. The study could provide baseline information on the significance of OM sequestration and preservation potential of mangrove ecosystems, and hence it is recommended to formulate sustainable management strategies to conserve the existing mangrove forest cover along the Kerala coast.